2011
DOI: 10.1136/bjsports-2011-090115
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of new versus recurrent sports concussions among high school athletes, 2005–2010

Abstract: Athletes sustaining recurrent concussions had longer symptom resolution times, were kept out of play longer and reported loss of consciousness more frequently than athletes sustaining new concussions. With the possibility of long-term impairment and other negative sequelae, proper management and prevention of concussions at the high school level is imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 33 publications
6
138
1
5
Order By: Relevance
“…Head impacts that resulted from contact with another player, the leading cause for concussion, 4,5,19,20 resulted in substantially greater head impact magnitude than head contact with other objects or surfaces among the team studied. Discussions of football safety occasionally suggest that player-to-player contact should be eliminated or that contact should be prohibited until players reach maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Head impacts that resulted from contact with another player, the leading cause for concussion, 4,5,19,20 resulted in substantially greater head impact magnitude than head contact with other objects or surfaces among the team studied. Discussions of football safety occasionally suggest that player-to-player contact should be eliminated or that contact should be prohibited until players reach maturity.…”
Section: Discussionmentioning
confidence: 99%
“…43 Symptoms include headache, dizziness, difficulty with concentration, confusion, nausea, and light sensitivity. 11,41 The majority of these symptoms resolve after 3-7 days. 25,38,51 There is some difference in presentation between the sexes: males have been more likely to present with amnesia, confusion, and disorientation, whereas females are more likely to experience drowsiness and noise sensitivity.…”
Section: Background On Concussionmentioning
confidence: 99%
“…11,39,41,59 Authors of a population-based study documented an incidence of approximately 1% for females and 1.9% for males. 68 Another study revealed that approximately 40% of emergency department visits for concussion involve children 8-13 years of age, and the remaining visits involve children 14-19 years of age.…”
Section: Epidemiological Factorsmentioning
confidence: 99%
“…In that intervening period, athletes may experience a combination of cognitive, somatic and emotional symptoms [9,10] that can impair their ability to complete school or work obligations [11]. Athletes who sustain more concussions are more likely to experience prolonged symptoms [12][13][14]. Even if the acute post-injury symptoms resolve there may be risk of harm later in life.…”
Section: Introductionmentioning
confidence: 99%